Paleoecology of fossil species of canids (Canidae, Carnivora, Mammalia) - Okřinová, Isabela (Jihočeská univerzita, 2014)
There were reconstructed phylogeny of recent and fossil species of subfamily Caninae in this study. Resulting phylogeny was used for examining possible causes of cooperative behaviour in Caninae. The study tried to explain evolution of social behavior in canids.
Paleoecology of fossil species of canids (Canidae, Carnivora, Mammalia)
Keywords: Caninae; fossil species; social behavior; Caninae; fossil species; social behavior